Effects of Polysaccharide Fucoidin on Cerebrospinal Fluid Interleukin-1 and Tumor Necrosis Factor Alpha in Pneumococcal Meningitis in the Rabbit - Granert, Carl (American Society for Microbiology, 1999)
The inflammatory response in bacterial meningitis is mediated by cytokines, such as tumor necrosis factor alpha (TNF-α) and interleukin-1 (IL-1), which are produced in the subarachnoid space by different cells, e.g., leukocytes, astrocytes, and microglia. The recruitment of leukocytes into the cerebrospinal fluid (CSF) has been shown to contribute to the neurological damage in this disease, a process which could be enhanced by treatment with antibiotics. In this study, we have used a rabbit meningitis model for two sets of experiments with intracisternal (i.c.) injections of Streptococcus pneumoniae. First, pneumococcal cell wall (PCW) components were injected i.c., inducing an inflammatory response with pleocytosis and increased levels of CSF TNF-α) and IL-1 at 6 and 12 h after PCW injection. Treatment with fucoidin, known to inhibit leukocyte rolling, abolished pleocytosis and inhibited the release of TNF-α and IL-1. In the second experiment, live pneumococcal bacteria were injected i.c. and treatment with one dose of ampicillin (40 mg/kg of body weight intravenously) was given 16 h after induction of meningitis, causing a sevenfold increase in CSF leukocytes over a 4-h period. CSF IL-1 levels at 16 h were high but did not increase further at 20 h. Also, CSF TNF-α levels were high at 16 h and tended to increase at 20 h. Fucoidin treatment prevented the antibiotic-induced increase of CSF leukocytes but had no effect on the TNF-α and IL-1 levels. Taken together, fucoidin reduced CSF TNF-α and IL-1 levels in acute bacterial meningitis induced by PCW fragments but had no effect later in the course of the disease, when live bacteria were used and an inflammatory increase was caused by a dose of antibiotics.